The relationship between symptomatic assessment and clinical signs of dryness in dry eye subjects - Ithnin, Mohd. Hafidz; Ariffin, Azrin Esmady; Mohd Kamal, Khairidzan (IIUM Press, 2017)
Introduction: There was no previous study to assess relationship between dry eye symptoms and signs in the local population. The purpose of this study is to evaluate the relationship of symptomatic assessment and clinical signs of dryness in dry eye subjects.